2021 Financial Sector Assessment Program Review : Background Paper On Scope. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2021)
This background paper reviews the development of the scope of financial stability assessments under the FSAP since the 2014 FSAP Review. The paper summarizes past experiences of such adaptation and observed trends with respect to the coverage of specific topics and then discusses possible directions to adjust the scope of future FSAPs over the next five years given the likely changes in the financial stability landscape. The paper also discusses collaboration with the World Bank as it pertains to the scope of financial stability assessments. It does not examine issues such as analytical approaches, participation, and resources, which are covered elsewhere in the FSAP Review.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: General Financial Markets; Monetary Policy; Political Economy